2017
DOI: 10.1007/s11230-016-9674-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiostoma norvegicum n. sp. (Nematoda: Angiostomatidae) a parasite of arionid slugs in Norway

Abstract: Angiostoma norvegicum n. sp. (Angiostomatidae) is described from the oesophagus, crop and the buccal mass of five species of slugs of the family Arionidae, Arion vulgaris (Moquin-Tandon), Arion ater (L.), Arion fasciatus (Nilsson), Arion fuscus (Müller) and Arion rufus/Arion ater hybrid), collected throughout Norway. Angiostoma norvegicum n. sp. was found parasitising arionids at seven of the 30 sample sites examined (23.3%), and 9.9% of all Arion spp. were infected with this nematode. The new species is chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…With the discovery of Angiostoma gandavensis n. sp., the total number of described species of the genus Angiostoma is now 19, of which 15 are described from molluscan hosts (Dujardin, 1845; Mengert, 1953; Morand, 1986, 1988, 1992; Morand and Spiridonov, 1989; Korol and Spiridonov, 1991; Morand and Barker, 1995; Luc et al ., 2005; Ivanova and Wilson, 2009; Ivanova and Spiridonov, 2010; Ross et al ., 2011, 2017). Several traits, such as stoma shape and structure, lateral allae and reproductive systems, have been found to be informative for identification within this genus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the discovery of Angiostoma gandavensis n. sp., the total number of described species of the genus Angiostoma is now 19, of which 15 are described from molluscan hosts (Dujardin, 1845; Mengert, 1953; Morand, 1986, 1988, 1992; Morand and Spiridonov, 1989; Korol and Spiridonov, 1991; Morand and Barker, 1995; Luc et al ., 2005; Ivanova and Wilson, 2009; Ivanova and Spiridonov, 2010; Ross et al ., 2011, 2017). Several traits, such as stoma shape and structure, lateral allae and reproductive systems, have been found to be informative for identification within this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Spiridonov, 1989; Korol and Spiridonov, 1991;Morand and Barker, 1995;Luc et al, 2005;Ivanova and Wilson, 2009;Ivanova and Spiridonov, 2010;Ross et al, 2011Ross et al, , 2017. Several traits, such as stoma shape and structure, lateral allae and reproductive systems, have been found to be informative for identification within this genus.…”
Section: Journal Of Helminthologymentioning
confidence: 99%
“…Moreover, international surveys have been conducted in Europe [7], Asia [43], North America [44], Australia [45] and Africa [46] to identify whether nematodes from other families are associated with molluscs as definitive hosts. Overall, it has been reported that nematode species belonging to the following eight families-Agfidae, Alaninematidae Alloionematidae, Angiostomatidae, Cosmocercidae, Diplogasteridae, Mermithidae and Rhabditidae used molluscs as definitive hosts [40,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Nematodes As a Biocontrol Agent Of Slugsmentioning
confidence: 99%
“…The Angiostoma genus has 18 known species, whereas Aulacnema is monotypic. Molluscan angiostomatids are obligate parasites of the intestine, hepatopancreas, oesophagus, buccal mass, crop, mantle cavity, salivary gland and pallial cavity (Ross et al ., 2016a, b). In addition to being molluscan angiostomatids, four species have, so far, been isolated from the intestine and bronchi of their amphibian and reptile hosts (Falcón-Ordaz et al , 2008).…”
Section: Nematodes Associated With Molluscs As Definitive Hostsmentioning
confidence: 99%